Studi Analisis 1 Yohanes 5:16-17 mengenai “Dosa yang tidak Mendatangkan Maut” - Heri Lim (TEMISIEN: Jurnal Teologi, Misi, dan Entrepreneurship, 2021)
The phrase 1 John 5:16-17 concerning "sin which brings death (ἁμαρτίαν πρὸς θάνατον)" and "does not bring death (ἁμαρτίαν μὴ πρὸς θάνατον)," has caused debate in the teachings of Christianity. The difficulties in this verse are found at least on three levels of debate. The first level is related to literary studies. The second level is related to its interpretation (hermeneutics), namely how to interpret sin that brings death and does not bring death. The third level of difficulty in this verse concerns the theological implications, namely how this verse influences the Christian life. Therefore this article aims to provide a perspective on how to understand the verse by elaborating on literary studies, looking at the options of interpretation that exist and their implications for the life of Christianity. AbstrakFrasa 1 Yohanes 5:16-17 mengenai “dosa yang mendatangkan maut (ἁμαρτίαν πρὸς θάνατον)” dan “tidak mendatangkan maut (ἁμαρτίαν μὴ πρὸς θάνατον),” telah menimbulkan perdebatan dalam ajaran kekristenan. Kesulitan dalam ayat ini ditemukan setidaknya pada tiga tingkat perdebatan. Tingkat pertama adalah terkait dengan kajian sastranya. Tingkat kedua adalah terkait dengan penafsirannya (hermeneutics), yakni bagaimana menafsirkan dosa yang mendatangkan maut dan tidak mendatangkan maut. Tingkat kesulitan ketiga dalam ayat ini menyangkut implikasi teologisnya, yaitu bagaimana pengaruh ayat ini kepada kehidupan kekristenan. Oleh karenanya artikel ini bermakud untuk memberi sudut pandang tentang bagaimana memahami ayat tersebut dengan cara mengelaborasi kajian sastranya, mencermati opsi penafsiran yang ada dan implikasinya bagi kehidupan kekristenan.